2020
DOI: 10.1002/cti2.1117
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor 7/8‐matured RNA‐transduced dendritic cells as post‐remission therapy in acute myeloid leukaemia: results of a phase I trial

Abstract: Objectives Innovative post‐remission therapies are needed to eliminate residual AML cells. DC vaccination is a promising strategy to induce anti‐leukaemic immune responses. Methods We conducted a first‐in‐human phase I study using TLR7/8‐matured DCs transfected with RNA encoding the two AML‐associated antigens WT1 and PRAME as well as CMVpp65. AML patients in CR at high risk of relapse were vaccinated 10× over 26 weeks. Results Despite heavy pretreatment, DCs of sufficient number and quality were generated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…OS was correlated with molecular and WT1-specific CD8 + CTL responses. Recently, Subklewe and colleagues 27 evaluated autologous DCs transfected with mRNAs (encoding the LAAs WT1 and preferentially expressed antigen in melanoma [PRAME] combined with HCMV-pp65 antigen) and matured with Toll-like receptor agonists. A first-in-human phase I study showed that DC administration to AML patients during remission and at high risk of relapse was feasible and safe and stimulated antigenic T cell responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OS was correlated with molecular and WT1-specific CD8 + CTL responses. Recently, Subklewe and colleagues 27 evaluated autologous DCs transfected with mRNAs (encoding the LAAs WT1 and preferentially expressed antigen in melanoma [PRAME] combined with HCMV-pp65 antigen) and matured with Toll-like receptor agonists. A first-in-human phase I study showed that DC administration to AML patients during remission and at high risk of relapse was feasible and safe and stimulated antigenic T cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, the manufacturing of DCs modified with mRNAs encoding WT1 for phase I and II clinical trials was feasible, and promising immunological and therapeutic effects against AML were observed. 27 , 39 Nevertheless, the manufacturing of these ex vivo -cultivated DC vaccines is complex and requires several steps and different types of GMP-grade reagents for antigen loading and maturation. We previously demonstrated feasibility of a 2-day protocol for GL manufacturing of iDCpp65 after CD14 + monocyte selection on CliniMACS and subsequent LV transduction in bags.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, mRNA-based DC vaccines have shown their potential in cancer applications in over 70 completed clinical trials. Recently, a phase I study where RNA transduced DCs were evaluated as a post-remission therapy in acute myeloid leukaemia (AML) was published [61] . This treatment induced an immune response with a positive relation between higher survival rate of patients with ≤ 65 years.…”
Section: Applicationsmentioning
confidence: 99%
“…However, these antigens may be found on nonhematopoietic tissues, resulting in on-target off-tumor toxicities. WT1 and PRAME are being evaluated in earlyphase clinical trials in patients with AML [11][12][13]. Strategies to identify additional antigens that are exclusively expressed on AML cells (including LSCs) includes comparing transcriptome and surfaceome data of AML cell lines, primary AML cells and healthy hematopoietic cells.…”
Section: Leukemia-associated Antigensmentioning
confidence: 99%